SERTÃO PRATICADO, SERTÃO REPRESENTADO: a caatinga como espaço de fartura ou privação, de ficar ou de passar - POTIER, ROBSON WILLIAM (Outros Tempos: Pesquisa em Foco - História, 2013)
The backland is not just a geographical space, bounded by borders politically well established and demarcated. If so, we would talk about "backlands", so in the plural, since, seen this way, they would be located in different areas, ranging in various states of our country, endowed with natural features and own relatively similar, but separated by boundaries border where "wilderness" was only what was contained in his constituency. The backland is much more than that.